Kajian Dampak Iklim Ekstrim Curah Hujan Tinggi (La-Nina) Pada Jeruk Siam (Citrus Nobilis var. Microcarpa) Di Kabupaten Banyuwangi, Jember Dan Lumajang - Ashari, Hasim; Hanif, Zainuri; Supriyanto, Arry (Universitas Muhammadiyah Yogyakarta, 2014)
Tangerine (Citrus nobilis var. microcarpa) is most widely cultivated Citrus in Indonesia, itâ€™s around 80% of all population of Citrus. Citrus can growth and cultivated in low land or upland (0-1500 m above sea level). Indonesia has extreme climate change (La Nina) in 2009 and 2010. Extreme climate change is one of the factors that affect the growth and productivity of citrus both in quality and quantity. Tangerine require 6-9 months of wet season and 3-6 months of dry season, although need enough water in dry season.Â This research aims to study the effect of extreme climate change with high rainfall on phenology, productivity and quality of Tangerine in Banyuwangi, Jember and Lumajang. This Research was conducted at Tangerine center from 2005 until 2011 using observation method, the tangerine that use was from 5 years after planted until 12 years after planted. The Result showed that high precipitation occurred in 2010 (without dry season) affect the phenology cycle from 1-3 times in a year until 4-6 times in a year, but not become a fruit due high flower drop. Itâ€™s cause a decrease in Productivity form 20-30 ton/h until 5-10 ton/h and also a decrease in quality (color, flavor and total dissolved solid). The result also showed that PJTKS system (Integrated Management for Healthy Tangerine) can prevent a decrease in Tangerine Productivity (10-12 ton/h). This Research also obtained that dry land and sandy land has potential for cultivation of tangerine that originally grown in paddy field.